DISTAL RADIUS GIANT CELL TUMOR EXCISION AND RECONSTRUCTION WITH AUTOGENOUS NON VASCULARIZED FIBULA GRAFT. - Ali Tauseef1, Arslan Ahmed Abro2, Asad Khan Gillzai3, Nouman Memon4, Hamidullah Khan5, Raza Mehmood6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
Distal radius is the third most common site of GCT (representing approximately 10% of all cases) typically affecting female gender, and mostly common in third and fourth decade of life. Distal radius site is the most locally aggressive one with higher possibility of recurrence (25 to 80%) and malignant transformation. METHODOLOGY; This is aprospective study, 11 patients were included in study out of which 7 were females and 4 were males, with mean age of 32 years. RESULTS; Patients who underwent enbloc excision of distal radius GCT excision and reconstruction with non-vascularized fibula graft have better early functional outcome. CONCLUSION; reconstruction of distal radius with non vascularized proximal fibula graft after enbloc resection of distal radius GCT is feasible, effective and reliable.